The prevalence of human papillomavirus in oropharyngeal cancer is increasing regardless of sex or race, and the influence of sex and race on survival is modified by human papillomavirus tumor status. Issue 5 (6th December 2018) - Faraji, Farhoud; Rettig, Eleni M.; Tsai, Hua‐Ling; El Asmar, Margueritta; Fung, Nicholas; Eisele, David W.; Fakhry, Carole
Abstract : Background: The purpose of this study was to evaluate the influence of sex and race/ethnicity upon prevalence trends of human papillomavirus (HPV) in oropharyngeal cancer (OPC) and survival after OPC. Method: This was a cohort study of patients included in the United States National Cancer Database who had been diagnosed with OPC between 2010 and 2015. Outcomes were HPV status of tumor specimens and overall survival. Sex‐ and race‐stratified trends in HPV prevalence were estimated using generalized linear modeling. The influence of sex, race, and HPV tumor status on overall survival was compared by Kaplan‐Meier method and Cox Proportional Hazards models. Results: This analysis included 20, 886 HPV‐positive and 10, 364 HPV‐negative OPC patients. The prevalence of HPV‐positive tumors was higher among men (70.6%) than women (56.3%) and increased significantly over time at a rate of 3.5% and 3.2% per year among men and women, respectively. The prevalence of HPV‐positive tumors was highest among whites (70.2%), followed by Hispanics (61.3%), Asians (55.8%), and blacks (46.3%). Blacks and Hispanics experienced significantly more rapid increases in prevalence of HPV‐positive tumors over time compared with whites (6.5% vs 5.6% vs 3.2% per year, respectively). In HPV‐positive OPC, neither sex nor race/ethnicity was associated with survival among patients with HPV‐positive OPC. In contrast, for HPV‐negative OPC, risk of death was significantly higher for women versus men (adjusted hazard ratio [aHR], 1.17; 95% confidence interval [CI], 1.08‐1.26) and blacks versus whites (aHR, 1.21; 95% CI, 1.10‐1.33). Conclusion: The prevalence of HPV‐positive tumors is increasing for all sex and race/ethnicity groups in the United States. Sex and race are independently associated with survival for HPV‐negative but not HPV‐positive OPC. Abstract : The prevalence of human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (OPC) is increasing for all sex and race/ethnicity groups in the United States. Sex and race are independently associated with survival for HPV‐negative but not HPV‐positive OPC.